Proximal to distal phalangeal articular angle of the first proximal phalanx: Reliability and correlation with round sign. Issue 8 (December 2022) - Lutz, Bernd; Kappe, Thomas; Reichel, Heiko; Taurman, Rita
Abstract: Background: To reduce the rate of correction loss in hallux valgus surgery, a proximal to distal phalangeal articular angle (PDPAA) of the proximal phalanx of the greater toe of> 8° is considered an indication for a combined Akin and Chevron osteotomy. The PDPAA is measured between the articular surfaces of the proximal phalanx of the greater toe. Viewed from a sagittal perspective, the joint surfaces are not perpendicular aligned to the phalanx axis. Therefore, the PDPAA might be confounded by pronation. This study aims to, first, evaluate the intra- and interobserver reliability of the PDPAA and, second, to analyze the correlation to first ray pronation. Methods: In a consecutive series of 59 feet who underwent hallux valgus (HV) surgery, PDPAA, round sign and other angles were measured on weight-bearing radiographs pre- and postoperatively. After power analysis, the intraclass correlation coefficient (ICC) was used to calculate the intra- and interobserver reliability. The correlation of PDPAA with the round sign as well as angles defining the HV and the Hallux valgus interphalangeus (HVI) were evaluated. Results: The PDPAA showed an excellent intra- and interobserver reliability (ICC 0.92 and 0.89, p < 0.05). The round sign did not correlate significantly with the PDPAA (p = 0.51). However, the PDPAA showed a moderate correlation with the interphalangeal angle (r = 0.51, p < 0.05) and fair inversely with the intermetatarsal angle (r = −0.45, p < 0.05). Conclusion: First, measurement of PDPAA is reliable. Second, PDPAA is not associated with first ray pronation, but a false low PDPAA is geometrically possible. A high PDPAA correlates with a relevant HVI and inversely correlates with the HV like the HVI. Hence, first ray pronation should be treated first and a remaining PDPAA of> 8° after intraoperatively reevaluation separately.